2023
DOI: 10.3390/biomimetics8010057
|View full text |Cite
|
Sign up to set email alerts
|

Chair Size Design Based on User Height

Abstract: General principles derived from anatomical studies of human body sizes should be applied to chair designs. Chairs can be designed for a specific user or a particular group of users. Universal chairs for public spaces should be comfortable for the largest possible group of users and should not be adjustable, such as office chairs. However, the fundamental problem is that the anthropometric data available in the literature either come from many years ago and are out of date or do not provide a complete set of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The authors concluded that the sit-to-stand movement pattern in obese subjects significantly differs from that in normal-weight subjects and is related to biomechanical and muscular factors (Galli et al 2000). In this case, even a slight increase in the seat's height significantly increases the comfort of getting up from the chair (Sydor and Hitka 2023). However, it is worth noting that a too-high seat remarkably reduces the comfort of sitting on the chair, so its height should not be excessive.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that the sit-to-stand movement pattern in obese subjects significantly differs from that in normal-weight subjects and is related to biomechanical and muscular factors (Galli et al 2000). In this case, even a slight increase in the seat's height significantly increases the comfort of getting up from the chair (Sydor and Hitka 2023). However, it is worth noting that a too-high seat remarkably reduces the comfort of sitting on the chair, so its height should not be excessive.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, extensive research have shown how ergonomics can actually be affected by gender segregation [ 79 , 80 ]. It has also been mentioned in a number of articles that differences in body shape exist not only in body size and body proportions, but also in gender [ 81 , 82 ]. Treaster & Burr have shown that women have been proven to be more susceptible to upper limb musculoskeletal disorders [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is understood from the literature that the relationships between the dimensions of the furniture and the user's anthropometric data are important in terms of ergonomics, strength, and functionality, and that the body weight of the users has a direct impact on the strength, especially in furniture used in public spaces [13][14][15]. Accordingly, it is of great importance to have acceptable design loads according to where a piece of furniture will be used and which kinds of service loads it will be exposed to, even during the design process.…”
Section: Discussionmentioning
confidence: 99%
“…The relations between the dimensions of the furniture and a user's anthropometric data is crucial for ergonomics, safety and functionality. The weight and dimensions of the user's body significantly affect the functional dimensions of the furniture, especially for overweight users [13,14]. It was stated that obesity, which has been a global epidemic in recent years, has significant effects on furniture design, especially in public spaces, and a study was conducted on the strength of chairs used by people with higher body mass [15].…”
Section: Introductionmentioning
confidence: 99%